Sing Street [videorecording (DVD)] - Carney, John, 1972-; Carney, John, 1972-; Boynton, Lucy; Thornton, Kelly; Walsh-Peelo, Ferdia (the Weinstein Company Home Entertainment, 2016)
See 1980s Dublin through the eyes of fourteen-year-old Conor, who is looking for a break from a home strained by his parents' relationship and money troubles while trying to adjust to his new inner-city public school where the kids are rough and the teachers are rougher. He finds a glimmer of hope in the mysterious, über-cool Raphina. With the aim of winning her heart he invites her to star in his band's music videos. There's only one problem: he's not part of a band yet.